STUDY THE CONTAMINATION OF SOME CHEMICAL POLLUTANTS IN HOT FOODS STORED IN PLASTIC BAGS AND CONTAINERS - Abu-Almaaly, R. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Plastic food containers and bags are classified as the most dangerous food and water contaminants around the world, because of the possibility to transfer the chemicals from it to food as a result of heating. Therefore this study was aimed to estimate the chemical pollutants (heavy metals included lead, cadmium, arsenic, mercury and zinc) that transfer from plastic food containers and bags to food. Thirty food containers (15 packages and 15 bags) synthesized from Polyethylene Terephthalate (PET) were purchased from the local market in Baghdad. Cut each into small equal pieces (0.5×0.5) cm and placed in a thermo glass containers then submerged 3 food solution (D.W, 3%, acetic acid, and olive oil). Two thermal treatments were done on it; the first one was carried out by boiling on a hot plate surface for 10 and 15 minutes, and the second by heating in microwave for 5 and 10 minutes, heavy metals were estimated by using Atomic Absorption technique. The results showed the significant difference between the concentration of the elements at level (pB>A after treated with two thermal treatment. The concentration of all heavy elements in this solution after heating for 10 minutes and heating in microwave for 5 and 10 minutes. Were higher than the acceptable limits by the Food and Drug Administration (FDA) and European Commission (EU).